Comparison of KP1019 and NAMI-A in tumour-mimetic environments. Issue 8 (27th July 2016) - Gransbury, Gemma K.; Kappen, Peter; Glover, Chris J.; Hughes, James N.; Levina, Aviva; Lay, Peter A.; Musgrave, Ian F.; Harris, Hugh H.
Abstract : Biotransformations of Ru(iii ) anticancer drugs are compared under a range of controlled hypoxia levels provided by spheroids at different sizes. Abstract : NAMI-A and KP1019 are Ru III -based anti-metastatic and cytotoxic anti-cancer drugs, respectively, and have been proposed to be activated by reduction to Ru II . The potential reduction of NAMI-A and KP1019 in the hypoxic environment of a tumour model of neuroblastoma was examined. Normoxic, hypoxic and necrotic tumour tissues were modelled by multicellular spheroids of SH-SY5Y human neuroblastoma cells of various diameters (50–800 μm). The variation in spheroid environment was confirmed with pimonidazole staining. Laser-ablation inductively-coupled plasma mass spectrometry showed KP1019 and NAMI-A penetration into the spheroid hypoxic region. XANES showed that the speciation of NAMI-A biotransformation products did not change significantly as hypoxia levels increased. KP1019 metabolites showed a correlation between the degree of spheroid hypoxia and the Ru K-edge energy consistent with either partial reduction of Ru III to Ru II in tumour microenvironments, increased S/Cl coordination or a reduced fraction of polynuclear Ru species. EXAFS spectroscopy was undertaken in an attempt to distinguish between these scenarios but was inconclusive.